Assembly of ZnII-coordination polymers constructed from benzothiadiazole functionalized bipyridines and V-shaped dicarboxylic acids: topology variety, photochemical and visible-light-driven photocatalytic properties. Issue 5 (17th January 2018) - Song, Wei-Chao; Liang, Ling; Cui, Xun-Zhe; Wang, Xiu-Guang; Yang, En-Cui; Zhao, Xiao-Jun
Abstract : Photocatalytic properties of four benzothiadiazole functionalized coordination polymers have been reported. Abstract : Four coordination polymers constructed from a benzothiadiazole functionalized bipyridine ligand bearing vinyl linkage 4, 7-bis(( E )-2-(pyridin-4-yl)vinyl)benzo[2, 1, 3]thiadiazole (bptda) with diverse conformations, namely, [Zn2 (bptda)(dpa)2 ] n (1 ), {[Zn2 (bptda)(oba)2 ]·2.75DMF} n (2 ), {[Zn4 (bptda)3 (oba)4 ]·2H2 O} n (3 ), and [Zn2 (bptda)(sdba)2 ] n (4 ), have been synthesized under solvothermal/hydrothermal conditions by tuning V-shaped aromatic polycarboxylate co-ligands possessing different bend angles (4, 4′-dicarboxydiphenylamine (H2 dpa), 4, 4′-oxybis(benzoic acid) (H2 oba), and 4, 4′-sulfonyldibenzoic acid (H2 sdba)). All the obtained complexes are based on binuclear secondary building units (SBUs), but exhibit different topologies. Complex1 presents a uninodal 3-fold interpenetratedjsm topology with the point symbol 5 10 ·6 4 ·7, complex2 shows a 6-connected threefold interpenetrated structure withpcu topology, complex3 presents a 2D + 2D → 3D polycatenation, and complex4 reveals a 2D + 2D → 2D twofold interpenetrating network with both polyrotaxane and polycatenane features. The effects of the bend angles of the V-shaped dicarboxylic acids on the diverse structures have been discussed. The thermal and luminescence properties of the complexes are investigated. The functionalization effect of thiadiazole groups on the optical absorption and visible-light-driven photocatalytic degradation of rhodamine B (RhB), methylene blue (MB), and crystal violet (CV) has been investigated.